Investigation of International News Sites in the Context of Neutrality in the News: The Example of Turkey’s Peace Spring Operation (Journal of Advanced Research in Social Sciences, 2019)
Internet journalism has brought a new impetus to journalism. The events in the world are instantly transferred to the reader / viewer on television channels, social media and internet news sites. There is a rivalry between the media tools at the speed of the transfer of news. International media organizations belonging to different capital groups, while conveying the news to the audience / reader in a fast manner, occasionally violating the reporting criteria; they ignore the principles of neutrality in the news. Specially, international media organizations often violate the principles of impartiality in their news when broadcasting news about different countries. In this study, we will investigate how the news websites of different countries, CNN International, France 24, Al Jazeera, TRT World and BBC news portals convey Turkey's Peace Spring Operation to their readers in 2019 in the context of the principles of neutrality in the news. A discourse analysis method will be used in the study.